The Impact Of Active Learning Strategies On Education And Learning Achievements/ استراتيجيات التعلّم النشط وأثرها في عملية التعليم والتحصيل الدراسي - Alkasem, Ahmad Abdulrahman; Mohamed, Yuslina (Ijaz Arabi Journal of Arabic Learning, 2025)
The world is undergoing rapid progress, leading to a significant knowledge revolution. This revolution has brought numerous technical and educational developments in educational institutions to improve learning through modern teaching strategies. The concept of "active learning" has gained popularity since the early 2000s due to the increasing scientific progress and interest in learning theories. Based on previous studies, researchers have reviewed active learning strategies and their impact on the learning and achievement process. The study investigated the importance of active learning methods and their effects on educational achievement. This was achieved by reviewing previous research on the subject, analyzing the perspectives of experts in the field, and employing a descriptive approach. The study was descriptive, reviewing previous research statements and findings and discussing the results of earlier studies. The researcher comprehensively analyzed earlier studies regarding their goals, tools, methodology, and results to achieve the study objective. The study concluded that active learning strategies are crucial to education and achievement. They promote deep understanding, critical thinking, and logical reasoning. Students are encouraged to develop skills for cooperation, networking, problem-solving, knowledge-building, and self-learning skills development. It also promotes interaction between teachers and students and their positive relationships. It promotes positive interaction between teachers and students, contributing to a balance between targeted education and students' autonomy. The study focuses on finding the right balance between targeted education and students' autonomy. After reviewing the research, most researchers recommended further studies to explore this area, develop effective active learning strategies, enhance teachers' skills in using these strategies, and create a checklist to evaluate the effectiveness of these strategies.